RESPONS PERTUMBUHAN DAN PRODUKSI BIOMASSA TANAMAN OBAT PEGAGAN (Centella asiatica (L.)Urb.) DENGAN PEMBERIAN FOSFOR DAN METIL JASMONAT. - Windy WS Manullang; J. A. Napitupulu J. A. Napitupulu; Mariati Mariati; Noverita SV Noverita SV (Jurnal Agroekoteknologi, 2013)
Response of Growth and Biomass Production of Medicinal Plants Centella (Centella asiatica (L.)Urb.) Phosphorus And Methyl jasmonate aplication. The aims of this study is determine theresponse of growth and biomass production of medicine plants Centella to aplications Phosphorusand Methyl jasmonate. For this purpose, field experiment had been done in January to June 2012 atdesa Syahmad Lubuk Pakam by using Randomized Block Design for growth variable whichphosphor application as single factor with 9 blocks and for component of biomass productionvariable used by Split Plot Design with factors, they are jasmonate rate (0;100;200 μM) andphosphor application as the sub plot (0,18,36,54 kg P2O5/ha). The growth and production charactersobserved were number of primary shoots, number of stolon, fresh and dry weight per sampel andfresh and dry weight per plot. The results showed that all characters were not significantly effectedby phosphorus and methyl jasmonate, significant interaction for both treatsments only at 11 weeksafter sawing for stolon numbers and the highest was found in combination of 100 μM jasmonateand without phsophorus.Keywords: centella asiatica, methyl jasmonate, phosphorus